Obstructive Sleep Apnoea in Stanford Type B Aortic Dissection Is Associated With Multiple Imaging Signs Related to Late Aortic Events - Zhang, Jiawei; Zhang, Zhe; Fu, Lingyu; Wang, Lei; Yang, Yu; Wang, Hao; Zhou, Baosen; Wang, Wei; Zhang, Jian; Xin, Shijie (Frontiers in Cardiovascular Medicine, 2021)
Background: Obstructive sleep apnoea (OSA) is highly prevalent in patients with Stanford type B aortic dissection (TBAD). Few studies have evaluated the effects of OSA on vascular changes in TBAD patients. This study aimed to explore the effect of OSA on aortic morphological changes in TBAD patients and its relation to late aortic events (LAEs). Methods: This case-control study included 143 TBAD patients. The diameters of different parts of the aorta were measured based on computed tomography angiography (CTA). According to the apnoea-hypopnoea index (AHI), OSA was classified as mild (5 ≤ AHI ≤ 15), moderate (15 < AHI ≤ 30), or severe (AHI > 30). The false lumen (FL) status was evaluated and classified as partially thrombosed, patent, or completely thrombosed. Results: The OSA prevalence in TBAD patients was 64.3%, and image differences related to LAEs between TBAD patients with and without OSA included the maximum aortic diameter at onset (37.3 ± 3.9 vs. 40.3 ± 4.5 mm, p < 0.001), the FL diameter of the proximal descending thoracic aorta (16.0 ± 6.8 vs. 20.3 ± 4.7 mm, p < 0.001), and the proportion of the FL that was partially thrombosed (39.2 vs. 64.1%, p = 0.004). Additionally, in the multivariable analysis of patients with OSA, the risks of an aortic diameter ≥40 mm, a proximal descending aorta FL ≥ 22 mm and a partially thrombosed FL were 4.611 (95% CI: 1.796–11.838, p = 0.001), 2.544 (95% CI: 1.050–6.165, p = 0.039), and 2.565 (95% CI: 1.167–5.637, p = 0.019), respectively, after adjustment for confounding factors. Trend tests showed that the risks of an aortic diameter ≥40 mm and a partially thrombosed FL increased with increasing OSA severity. Conclusions: TBAD patients with moderate to severe OSA have aortic dilatation in different parts of the aorta. OSA is an independent risk factor for multiple imaging signs related to LAEs, suggesting that OSA is an important factor affecting the prognosis of TBAD patients.